MODERASI NEGATIVE EMOTION PADA PENGARUH JOB INSECURITY TERHADAP EMPLOYEE ENGAGEMENT DI PT DELTA SATRIA DEWATA - Tahir, Clarissa Amalia; Putra, Made Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Employee engagement is related to the company's overall performance and is defined as an employee's emotional commitment to their workplace. PT. Delta Satria Dewata still finds problems related to employee engagement. Another problem is job insecurity that occurs because of a third party or outsourcing that makes employees feel insecure, especially in employee contracts that cause negative emotions. This study aims to determine the effect of job insecurity on employee engagement and the role of negative emotion as a moderator variable. The population in this study were employees of PT. Delta Satria Dewata totals 120 people and the method of determining the sample used is saturated sampling. Data were collected using a questionnaire and measured using a Likert scale. The data analysis used in this study is MRA. The results of this study indicate that job insecurity has a negative and significant effect on employee engagement, while negative emotion strengthens the relationship between job insecurity and employee engagement. The results of this study are in line with the results of previous studies and theoretical studies of two factors related to employee engagement